2022
DOI: 10.1002/dad2.12298
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers for cognitive decline and clinical progression in a Mexican American cohort

Abstract: Introduction : The clinical translation of biofluid markers for dementia requires validation in diverse cohorts. The study goal was to evaluate if blood biomarkers reflecting diverse pathophysiological processes predict disease progression in Mexican American adults. Methods : Mexican American adults (n = 745), 50 years of age and older, completed annual assessments over a mean of 4 years. Serum collected at baseline was assayed for total tau, neurofilament light (NFL), ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
7
10
0
Order By: Relevance
“…In line with our observations, plasma GFAP levels have been reported to be positively associated with cognitive dysfunction and cerebral atrophy 18,33,34 . These clinical observations t well with pathology studies that show a gradual increase of GFAP levels in the brain in relation to AD severity 35,36 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our observations, plasma GFAP levels have been reported to be positively associated with cognitive dysfunction and cerebral atrophy 18,33,34 . These clinical observations t well with pathology studies that show a gradual increase of GFAP levels in the brain in relation to AD severity 35,36 .…”
Section: Discussionsupporting
confidence: 92%
“…These clinical observations t well with pathology studies that show a gradual increase of GFAP levels in the brain in relation to AD severity 35,36 . Plasma GFAP levels have also been reported to associate with longitudinal cognitive decline and cerebral atrophy, which is con rmed in our study, [37][38][39][40] and higher incident dementia risk 26,33 . Thus, familial, clinical, and population-based studies suggest that increased plasma or serum GFAP levels not only associate with, but also predict, disease progression in AD.…”
Section: Discussionsupporting
confidence: 85%
“…In line with our observations, plasma GFAP levels have been reported to be positively associated with cognitive dysfunction and cerebral atrophy 18,42,43 . These clinical observations fit well with pathology studies that show a gradual increase of GFAP levels in the brain in relation to AD severity 44,45 .…”
Section: Discussionsupporting
confidence: 92%
“…These clinical observations fit well with pathology studies that show a gradual increase of GFAP levels in the brain in relation to AD severity 44,45 . Plasma GFAP levels have also been reported to associate with longitudinal cognitive decline and cerebral atrophy, which is confirmed in our study, [46][47][48][49] and higher incident dementia risk 35,42 . Thus, familial, clinical, and population-based studies suggest that increased plasma or serum GFAP levels not only associate with, but also predict, disease progression in AD.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, plasma glial fibrillary acidic protein (GFAP), a marker of astrogliosis, 65 , 66 is elevated across the Alzheimer’s spectrum, 67-71 as well as other neurodegenerative diseases such as frontotemporal dementia 70 , 72 and studies report a significant correlation with cognitive functioning. 37 , 62 , 68 , 70 , 72-74 Plasma GFAP has also been reported to increase over time in cognitively unimpaired individuals; 75 , 76 however, fewer studies have investigated its relationship with cognitive functions in late-adulthood individuals without dementia. One study reported a significant inverse association with cross-sectional working memory and executive functioning, 75 and in the same cohort, a significant correlation was reported with cognitive functions at a 12-month follow-up.…”
Section: Introductionmentioning
confidence: 99%